PENGARUH PRODUCT PLACEMENT KOPIKO TERHADAP PURCHASE INTENTION MELALUI BRAND AWARENESS SEBAGAI VARIABEL MEDIASI - Vindha Fajar Ethika; Sonja Andarini; Rusdi Hidayat Nugroho; Budi Prabowo (STKIP Persada Khatulistiwa Sintang, 2022)
The increasing number of viewers for Korean dramas is an opportunity for companies to collaborate and promote and advertise their products. South Korean companies take advantage of the popularity of Korean dramas to advertise their products by including products in dramas. This study aims to analyze and examine the effect of placing Kopiko candy products in Korean dramas on buying interest with brand awareness as a mediating variable. This research is included in the type of quantitative research through a descriptive approach. The population that is the target of this research is the people of Surabaya who have watched or been exposed to the Korean drama “Vincenzo” and or “Hometown Cha-cha-cha”, from that population, 100 samples of respondents were taken. For the sampling technique, the researcher uses a purposive sampling technique which is included in the non-probability sampling method. Meanwhile, in the data analysis technique, the researcher used path analysis techniques, Sobel hypothesis testing techniques and t-test. The research that has been done has concluded that there is a positive and significant influence between Product Placement on Kopiko's Purchase Intention in Surabaya through the Brand Awareness variable.